Electrodeposited WS2 monolayers on patterned graphene. (10th December 2021) - Noori, Y J; Thomas, S; Ramadan, S; Greenacre, V K; Abdelazim, N M; Han, Y; Zhang, J; Beanland, R; Hector, A L; Klein, N; Reid, G; Bartlett, P N; et al.
Abstract: The development of scalable techniques to make two-dimensional (2D) material heterostructures is a major obstacle that needs to be overcome before these materials can be implemented in device technologies. Electrodeposition is an industrially compatible deposition technique that offers unique advantages in scaling 2D heterostructures. In this work, we demonstrate the electrodeposition of atomic layers of WS2 over graphene electrodes using a single source precursor. Using conventional microfabrication techniques, graphene was patterned to create micro-electrodes where WS2 was site-selectively deposited to form 2D heterostructures. We used various characterization techniques, including atomic force microscopy, transmission electron microscopy, Raman spectroscopy and x-ray photoelectron spectroscopy to show that our electrodeposited WS2 layers are highly uniform and can be grown over graphene at a controllable deposition rate. This technique to selectively deposit transition metal dichalcogenides over microfabricated graphene electrodes paves the way towards wafer-scale production of 2D material heterostructures for nanodevice applications.